Pembuatan dan Pengujian Alat Penetas Telur Bertenaga Surya Tegangan 12V DC - Nuban, Jondri K. A.; Koehuan, Verdy A.; Selan, Rima N.; Tobe, Adi Y. (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2024)
produce quality poultry chicks. However, the natural egg-hatching process is often less efficient and susceptible to fluctuations in environmental temperature. Therefore, to increase the efficiency and results of egg hatching, this research aims to design and test an automatic chicken egg incubator that uses solar energy. This tool is designed to consider factors such as temperature, humidity, and air circulation required for optimal egg hatching. Testing was carried out for 21 days, by monitoring environmental temperature, humidity, and temperature distribution in the egg hatching room. The test results showed that the tool was able to reach the desired temperature for hatching eggs and succeeded in hatching several eggs well, while some other eggs experienced defects or died during the hatching process. In addition, power and energy consumption analysis shows that the device has quite good efficiency in using energy, with low energy consumption to maintain the room temperature within the desired range. The solar-powered automatic egg incubator has the potential to increase the efficiency and yield of egg hatching in the livestock industry and can be an environmentally friendly alternative by utilizing solar energy which is available freely and sustainably